Increasing Economic Efficiency When Creating a Dynamic Microclimate in Compressed Conditions of Production Premises - Voznyak, Orest; Spodyniuk, Nadiia; Sukholova, Iryna; Savchenko, Olena; Dovbush, Oleksandr; Kasynets, Mariana (Green and Low-Carbon Economy, 2025)
This work is devoted to increasing economic efficiency when using two-stream air distributors that form a swirled and flat stream while providing a dynamic microclimate in compressed conditions of industrial premises. The design of a two-jet air distribution (TJAD) is proposed, which forms a swirled and flat laying air jet that provides intensive attenuation of air flow velocity and temperature in stationary and variable mode. Measures aimed at saving cold energy are considered, namely, air supply in a variable mode, use of the flooring effect, and use of devices for intensification of tidal flow turbulence. A set of optimal measures for obtaining the maximum economic effect is determined. A method of development and calculation of inflow mechanical ventilation systems based on the specified air distributors is proposed. The economic evaluation of the use of air distribution devices proved that the use of a TJAD makes it possible to obtain some economic effect. Received: 4 September 2023 | Revised: 18 October 2023 | Accepted: 28 January 2024 Conflicts of Interest The authors declare that they have no conflicts of interest to this work. Data Availability Statement The data that support the findings of this study are openly available in AKJounals at https://doi.org/10.1556/606.2021.00419, reference number [11], in Naukovyi Visnyk Natsionalnoho Hirnychoho Universytetu at https://doi.org/10.33271/nvngu/2021-2/104, reference number [10], and in Sciendo at https://doi.org/10.30657/pea.2021.27.22, reference number [8]. Author Contribution Statement Orest Voznyak: Conceptualization, Data curation, Writing - original draft, Supervision, Project administration. Nadiia Spodyniuk: Validation, Formal analysis, Writing - review & editing. Iryna Sukholova: Methodology, Investigation, Resources. Olena Savchenko: Software, Formal analysis, Visualization. Oleksandr Dovbush: Data curation, Visualization. Mariana Kasynets: Investigation, Resources.